The degree of availability of social skills and teamwork in the new reform curricula for the end of primary education, from the point of view of primary school principals. - Messeguem, elhamlaoui (Journal of Social Sciences and Humanities, 2024)
This study aimed to build a list of the most important social skills and teamwork that are required to be available in the new reform curricula for the end of the primary education stage. From the point of view of the principals of primary education and those affiliated with the schools of the municipalities of Messila and Bousaada, and to the differences according to the variables of gender, professional experience, educational level, and training style. The study reached the following results: The degree of availability of social skills and teamwork that are included in the curricula of the new reforms of the curricula of the end of the primary education stage is highly.